2019
DOI: 10.1002/srin.201900475
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Lubricating Physical Vapor Deposition Coatings for Dry Cold Massive Forming

Abstract: Cold massive forming, particularly forward extrusion of steel, is characterized by high material utilization, product quality, and resource efficiency. Currently, enormous quantities of mostly ecologically harmful lubricants are required, leading to the demand for lubricant-free cold forming. Furthermore, cost savings are achievable due to shorter lead times. However, the requirements for the tools cannot be met without the application of wear-resistant and friction-reducing hard coatings. The self-lubricating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…PVD self-lubricating (Cr,Al)N+Mo:S and (Cr,Al)N+W:S hard coatings offer high potential for application on cold forming tools. Bobzin et al [169] characterised self-lubricating tool coatings based on (Cr,Al)N, which were modified with W and S, as well as Mo and S. Coatings introduced with Mo and S showed much better adhesion between the coating and the substrate compared to the systems modified with W and S. Showing excellent adhesion to the substrate, a significant reduction in COF and high wear resistance, the (Cr,Al)N+Mo:S coatings demonstrated the highest potential for use on deep drawing tools. The self-lubricating properties of PVD-deposited tool coatings are based on the formation under tribological loads of reactive layers consisting of friction-reducing transition metal dichalcogenides.…”
Section: Self-lubricating Materials and Coatingsmentioning
confidence: 99%
“…PVD self-lubricating (Cr,Al)N+Mo:S and (Cr,Al)N+W:S hard coatings offer high potential for application on cold forming tools. Bobzin et al [169] characterised self-lubricating tool coatings based on (Cr,Al)N, which were modified with W and S, as well as Mo and S. Coatings introduced with Mo and S showed much better adhesion between the coating and the substrate compared to the systems modified with W and S. Showing excellent adhesion to the substrate, a significant reduction in COF and high wear resistance, the (Cr,Al)N+Mo:S coatings demonstrated the highest potential for use on deep drawing tools. The self-lubricating properties of PVD-deposited tool coatings are based on the formation under tribological loads of reactive layers consisting of friction-reducing transition metal dichalcogenides.…”
Section: Self-lubricating Materials and Coatingsmentioning
confidence: 99%
“…In addition, their application is also restricted by its low loadbearing capacity, poor coating adhesion and low hardness [23]. A promising approach to overcome these restrictions, is to combine PVD hard coating with elements which are able to form selflubricating TMD structures under tribological loads [4].…”
Section: Tmds As Example For Lubricants With Layer Lattice Structurementioning
confidence: 99%
“…This possibility is estimated by the current oil lubrication market at $ 18.7 bn for the USA alone [3]. Friction reducing PVD coatings can be used either as alternative for lubricants or as a further support for highly loaded tribological systems [2,4]. Overall, it is not only a challenge to develop hard coatings with a self-lubricating effect, but also to meet the thermal requirements that lead to their activation and maintenance [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, nitride-based hard composite coatings produced by physical vapor deposition (PVD) deposition offer high hardness, wear, and corrosion resistance that increase tool life. [12][13][14][15] Kumar et al 16 reported that TiN coated AISI O1 cold work tool steel had 53.5% and 308% higher elastic modulus and hardness than simply heat-treated steel, respectively, and TiN coated steel had only about two times lower wear rate. According to Hsu et al, 17 a mixed-phase (Ti, Al) N coated AISI D2 cold work tool steel produced by concurrently using Ti and Ti-Al alloy targets in the cathodic arc process increased abrasion resistance by about 5 times.…”
Section: Introductionmentioning
confidence: 99%